The Effect of CIRC Combined with Guided Inquiry Learning Model on Scientific Literacy in Terms of Academic Ability - Fabella Dwi Budiartiningsih; Maridi Maridi; Slamet Santosa (Universitas Sebelas Maret, 2020)
Scientific literacy is the ability to use scientific knowledge, identify questions, and draw conclusions based on scientific evidence. Purpose: This study was aimed to know: (1) the influence of guided inquiry learning combined with the CIRC model on scientific literacy; (2) the influence of academic ability on the scientific literacy; (3) the interaction between learning model and academic ability to the scientific literacy. Methods: The research was quasi-experiment research. The population of this research was all of the 11th-degree students at SMA N 2 Boyolali in the academic year 2019/2020. The sample of this research was students of XI MIPA 1 as the first experimental group and XI MIPA 2 as the second experiment group. The data was collected by test techniques (NOSLiT). Result: The hypotheses analyzed by Anova Two Ways with the level of significance 5%. The results showed that there was an influence of the use of guided inquiry learning with CIRC models to scientific literacy (Sig. = 0.000) < α = 0.05. There was the influence of academic ability toward scientific literacy (Sig. = 0.000) < α = 0.05, and there was no effect interaction between learning- models and academic ability their scientific literacy (Sig. = 0.020) > α = 0.05. Conclusion: The research concluded that 1) guided inquiry learning combined with the CIRC model had a significant effect on scientific literacy, 2) the academic ability has a significant effect on competency of scientific literacy, 3) the interaction of learning models and academic abilities do have a significant effect on students' scientificliteracy